2013
DOI: 10.1002/hyp.9871
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for extreme variations in the permeability of laterite from a detailed analysis of well behaviour in Nigeria

Abstract: Abstract:Laterite soils are widespread in tropical Africa and have a large impact on the hydrology of the areas they cover. The permeability of laterite helps determine the partitioning of runoff and interflow and regulates groundwater recharge to underlying bedrock. Groundwater within laterite also forms a widespread source of drinking water, typically from unimproved hang-dugwells. Despite its importance, there is little published information on laterite aquifer properties. In this study, data from a 6 m dee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 41 publications
2
26
0
Order By: Relevance
“…Very rapid horizontal pathways exist in the shallow tropical soil zone, which may be laterally extensive, in some cases providing transmissivities in excess of 300 m 2 /day (Bonsor et al 2014). Rapid vertical pathways also exist due to the presence of natural macropores, e.g.…”
Section: Urban Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…Very rapid horizontal pathways exist in the shallow tropical soil zone, which may be laterally extensive, in some cases providing transmissivities in excess of 300 m 2 /day (Bonsor et al 2014). Rapid vertical pathways also exist due to the presence of natural macropores, e.g.…”
Section: Urban Populationmentioning
confidence: 99%
“…Separation distances of 10-50 m were commonly recommended; however, there was no detailed consideration of higher-risk settings such as those posed by tropical soils, which cover a considerable part of Africa, or karstic settings which require considerably greater separation distances (e.g. Bonsor et al 2014).…”
Section: Separation Between Sources Of Pollution and Groundwater Abstmentioning
confidence: 99%
See 1 more Smart Citation
“…Lohani et al (2011) {13] investigated the aquifers of Jatni area and reported that GWT of the area lies in fractures and sedimentary sandstone in succession within laterite and old alluvium of Holocene epoch. Bonsor et al, (2014) [14] reported that the quantity and quality of GW are influenced by permeability properties of Laterites which partition the surface runoff and interflow. Mishra et.…”
Section: +4mentioning
confidence: 99%
“…Oju/Obi is a remote part of SE Nigeria and experiences severe water shortages during the annual dry season, despite a high average annual rainfall of c. 1600 mm (Davies & MacDonald 1999). The area has been subject to extensive groundwater investigations in an attempt to improve the stubbornly high rates of guinea worm infection and low water supply coverage (MacDonald et al 2001(MacDonald et al , 2005(MacDonald et al , 2008Bonsor et al 2014). Oju/Obi is situated within the lower section of the Benue Trough, a major elongated geological rift structure infilled with fine-grained, low-permeability Cretaceous sediments (Ofoegbu 1985).…”
Section: Study Areamentioning
confidence: 99%